Myakush B.M, Kshyvetskyy B.Y. The effect of temperature on shape stability of three-layer parquet boards. - М’якуш, Б.М.; Кшивецький, Б.Я. (Problems of Tribology, 2016)
During operation, parquet board is exposed to various kinds of external factors that will influence its shape stabil-ity. Some major factors among them are temperature, moisture, and load that a parquet board takes during operation. Each of these factors will affect the shape stability in different ways, but long-term or their combined action can lead to change in its properties or destruction of the floorboard. Therefore, studying the influence of moisture, temperature, and load on the shape stability of parquet board is of great importance In our study of shape stability, the three-layer parquet board is considered as a construction made from wood and adhesive. Software of integrated CAD/CAE systems was used for mathematical modeling and simulation of temperature in-fluence on shape stability of three-layer parquet boards, while the output parameters were physical and mechanical properties of the wood and adhesive and the geometry of the specimen. These properties may change during operation, so they are de-terminative for the shape stability of the parquet board.Based on the visualization and graphic curves of deformation σх and σу of the study construction of the parquet board depending on the temperature change, it was found that the maximum stress is achieved in the near-surface regions of the first and third layers of the board. The minimum stress is observed in the second layer of the structure. In the first and third layers of elements, the rise of normal stresses is observed, while the second layer experiences a decrease in normal stresses. The second layer is characterized by a uniform distribution of normal stresses, which is caused by the influence of the adhesive layers. However, the strain distribution in the cross section of the structure is nonuniform, since a decrease of deformations in the near-surface layers of the construction occurs and stabilization of the deformation in the second layer of the structure is observed. The reduced stiffness of the material of the second layer is due to the slowdown in the growth of stresses in that layer. The increase in stiffness of the first layer is due to a significant increase of stresses in it compared to the middle layerThe results of the analysis found that the shape stability of three-layer boards, depending on the temperature, changes differently. The main load will be taken by the middle layer of the parquet board, which will have a significant im-pact on the shape stability of the floorboard during operation.Keywords: three-layer parquet board, shape stability, stress-strain state, mathematical model, graphic curves, adhesive, wood.